Interactions between International Migration and the Welfare State - Assaf Razin; Efraim Sadka (Center for Economic Studies and ifo Institute (CESifo), 2000)
The intratemporal redistribution feature of the welfare state makes it an attractive destination for immigrants, particularly for low-skill immigrants. George Borjas (1994) reports that foreign-born households in the United States accounted for 10 percent of households receiving public assistance in 1990, and for 13 percent of total cash assisitance distributed, even though they constituted only 8 percent of all households in the United States. In this chapter we explore the implications of various redistribution policies for the attitude of the native-born towards migrants. We analyze the effect of migration on the shape and magnitude of redistribution policies that are determined in a political economy equilibrium; at the same time, we address the question whether the level of migration, when not restricted, is higher or lower in this welfare state than in the laissez-faire (no-redistribution) economy.
Keywords: 330